2021
DOI: 10.3389/fonc.2020.563613
|View full text |Cite
|
Sign up to set email alerts
|

Tissue MicroRNA Expression as a Predictor of Response to Immunotherapy in NSCLC Patients

Abstract: IntroductionExpression of PD-L1 protein on tumor cells, which is so far the only validated predictive factor for immunotherapy, is regulated by epigenetic and genetic factors. Among the most important ones that regulate gene expression are microRNAs.Materials and MethodsThe study included 60 patients with NSCLC who underwent first or second line immunotherapy with pembrolizumab or nivolumab. FFPE materials were collected before the start of immunotherapy. We examined relative expression of microRNAs (miR-141, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…However, innate or acquired pharmacological resistance represents important obstacles to overcome. As well-documented, noncoding RNAs including circular RNAs (circRNAs) and microRNAs (miRNAs) are one of the pharmacological resistance mechanisms in tumor cells [8,9]. Cisplatin (DDP) is the backbone of first-line chemotherapy for NSCLC [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, innate or acquired pharmacological resistance represents important obstacles to overcome. As well-documented, noncoding RNAs including circular RNAs (circRNAs) and microRNAs (miRNAs) are one of the pharmacological resistance mechanisms in tumor cells [8,9]. Cisplatin (DDP) is the backbone of first-line chemotherapy for NSCLC [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the decreased expression of the miR-200 family in cancer tissues [ 18 , 19 ], and anti-cancer drug-resistant cancer cells [ 93 ]. The expression levels of miR-200 family miRNAs were shown to predict responses to anti-cancer therapeutics [ 19 , 20 , 21 , 22 , 23 , 24 ]. Thus, miR-200 family miRNAs can be a target for anti-cancer drug development.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of the miR-200 family were strongly associated with better survival of bladder cancer patients [ 23 ]. The high expression of miR-200b was correlated with better responses of lung cancer patients to immunotherapy involving anti-PD-l antibodies such as pembrolizumab [ 24 ].…”
Section: Mir-200 Family As a Diagnostic And Prognostic Markermentioning
confidence: 99%
“…Several studies have focused on the value of micro RNAs and non-coding RNAs for the prediction of responses to ICIs. Several tissue-extracted microRNAS such as miR-200b and miR-508 appear as positively correlated with the response to ICIs, while others such as miR-429 are negative biomarkers [ 72 ]; however, this did not remain significant after multivariate analysis when compared to PD-L1 expression. Based on a large cohort of NSCLC patients, a model combining seven non-coding RNAs significantly stratified patients into immune-cold and immune-hot cohorts, remained independent from other clinical/biological features and could complete the PD-L1 expression as a biomarker [ 73 ].…”
Section: Genomics Transcriptomics and Proteomics: Understanding The C...mentioning
confidence: 99%